1994
DOI: 10.1161/01.cir.89.4.1810
|View full text |Cite
|
Sign up to set email alerts
|

Functional improvement precedes structural regression of atherosclerosis.

Abstract: Abnormal vasoconstrictor responses to serotonin usually return to or toward normal within a few months during regression of atherosclerosis. Functional improvement occurs in conjunction with early resorption of lipid from the arterial wall and occurs before detectable changes in mass of the atherosclerotic lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 40 publications
6
33
1
2
Order By: Relevance
“…Notably, in our study, only KP was able to prevent the development of a blunted kidney vasodilatory reserve, which confers adjunctive beneficial effects in the protection of the kidney. Similar to what happens in the periphery, changes in renal endothelium-dependent dilation could precede structural changes (31,32).…”
Section: Subanalysis For Agementioning
confidence: 87%
“…Notably, in our study, only KP was able to prevent the development of a blunted kidney vasodilatory reserve, which confers adjunctive beneficial effects in the protection of the kidney. Similar to what happens in the periphery, changes in renal endothelium-dependent dilation could precede structural changes (31,32).…”
Section: Subanalysis For Agementioning
confidence: 87%
“…In addition to vascular tone, the endothelium regulates cell adhesion, platelet aggregation, coagulation, lipid transport and oxidation, inflammation, and mitogenesis (6). Changes in EDD precede structural changes during experimental induction or regression of atherosclerosis in monkeys (7). Endothelial function in patients who have undergone KP transplantation is normal; this could be the result of the reduction of the atherothrombotic state.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, endothelium modulates platelet adhesion, macrophage migration, lipid transport, and mitogenesis (6). Impairment of dilation ability is an important predictor of atherosclerosis and its complications (7). Diabetes, uremia, and hyperhomocystinemia are conditions with known increased proneness toward EDD (8).…”
mentioning
confidence: 99%
“…In previous studies, we demonstrated that this diet produces both hyperhomocyst(e)inemia and hypercholesterolemia, with moderately severe atherosclerotic lesions in large vessels. 11,28 We anticipated that infusion of thrombin might generate higher levels of APC in atherosclerotic monkeys than in monkeys fed the control diet, because we previously observed increased protein C activation in explants of aorta and carotid artery from atherosclerotic monkeys. 11 In contrast to our expectations, however, levels of circulating APC were almost 20% lower after infusion of thrombin in atherosclerotic monkeys than in control monkeys.…”
Section: Lentz Et Al Impaired Anticoagulation In Atherosclerosismentioning
confidence: 99%